Target height prediction in Indonesian children: a population-based and clinically relevant model - Moelyo, Annang Giri; Ferdian, Hanum (Paediatrica Indonesiana, 2025)
Background The traditional calculation of target height (TH) overlooks two important factors: the assortative mating correlation, which reflects the tendency for people of similar height to partner, and the parental–offspring correlation, which measures the strength of the relationship between parents’ and children’s heights. A more accurate model is needed for the Indonesian population.   Objective To develop a target height (TH) prediction model for Indonesian children and to compare its performance with traditional formulas. Methods This retrospective study used nationally representative data from the Indonesia Family Life Survey (IFLS). Adult height data from the IFLS-5 (2014) for 2,506 subjects and the corresponding parental height data from the IFLS-3 (2000) were analyzed. We used a new model, namely estimated target height (eTH), which combined the Hermanussen–Cole and van Dommelen methods, to estimate each participant’s TH. This new model was compared to traditional models which used Tanner (TTH) and modified Tanner (mTH) formulas.   Results The new eTH model yielded the following formulas: TH (boys) = 0.36 × father’s height + 0.43 × mother’s height + 42.77; and TH (girls) = 0.30 × father’s height + 0.36 × mother’s height + 50.47. Correlations with the observed adult height were highest for the new model (r = 0.528 for boys; r = 0.534 for girls), compared to traditional models. Conclusion This study provides a locally validated model for TH estimation in Indonesian children that demonstrates improved clinical applicability over traditional formulas.